ANALISIS FAKTOR PENYEBAB TINGGINYA ANGKA KASUS CERAI GUGAT/KHULU’ DI PENGADILAN AGAMA KELAS 1A KOTA TERNATE : ANALISIS FAKTOR PENYEBAB TINGGINYA ANGKA KASUS CERAI GUGAT/KHULU’ DI PENGADILAN AGAMA KELAS 1A KOTA TERNATE - Stomer, Alfandi; Abdul Djalal, Marini; Abdullah, Baharuddin; Abbas, Abdul Haris; Harwis, Harwis (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2023)
The reason for the high rate of divorce and divorce is no longer unstoppable, this is due to a shift in social values in society. In the last three years, the total data from 2019- 2021 was 1,929 cases consisting of 1,313 cases of contested divorce and 616 cases of talak divorce. The formulation of the problem in this research is what factors cause lawsuit divorce and analysis of the causes of the high number of lawsuit divorce cases in the Religious Courts. The type of research used is empirical juridical research using two approach methods, namely the statutory approach and the case approach, using data collection techniques by means of observation, interviews and documentation. The research results explain that first, there are four factors that cause divorce, including educational factors, economic factors, legal awareness factors, and parental interference factors. Second, of the several factors that cause divorce, the reason for the high number of divorce cases is an inseparable part of the reasons for divorce as stated in Law of the Republic of Indonesia Number 16 of 2019 concerning Marriage and also Government Regulation Number 9 of 1975 concerning Implementation of the Law. Law of the Republic of Indonesia Number 1 of 1974 concerning Marriage.